2016
DOI: 10.14814/phy2.12961
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone treatment decreases hepatic glucose production and renal reabsorption of glucose in alloxan-induced diabetic Wistar rats

Abstract: The thyroid hormone (TH) plays an important role in glucose metabolism. Recently, we showed that the TH improves glycemia control by decreasing cytokines expression in the adipose tissue and skeletal muscle of alloxan‐induced diabetic rats, which were also shown to present primary hypothyroidism. In this context, this study aims to investigate whether the chronic treatment of diabetic rats with T3 could affect other tissues that are involved in the control of glucose homeostasis, as the liver and kidney. Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(38 reference statements)
1
7
0
1
Order By: Relevance
“…Moreover, body weight gain was decreased in these animals, in agreement with a recent study, which demonstrated that T3 treatment reduces the adiposity and increased the lean mass of obese mice (da Silva Teixeira et al. ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, body weight gain was decreased in these animals, in agreement with a recent study, which demonstrated that T3 treatment reduces the adiposity and increased the lean mass of obese mice (da Silva Teixeira et al. ).…”
Section: Discussionsupporting
confidence: 91%
“…; Teixeira et al. ). It is relevant to stress that this dose of T3 treatment did not change the hemodynamic parameters in comparison to the control group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with work on Wistar rats with diabetes induced by alloxan treated with T3 (Teixeira et al . ). These rats had reduced glucose production in conjunction with the reduced expression of GLUT2.…”
mentioning
confidence: 97%